Optimization of Extrusion Conditions and Cooked Vegetable-Chicken Mixture for Instant Banana-Vegetable Soup Powder - Ainebyona, Paddy; Kigozi, Julia; Mukisa, Ivan M. (European Journal of Agriculture and Food Sciences, 2021)
Instant soups are preferred by consumers for their flexibility in preparation and longer storage life. Extrusion cooking is one of the recent developments reported to improve nutrient content of soups. However, little information is available regarding use of extrusion cooking in development of banana vegetable soups. This study investigated the use of extrusion cooking in production of instant banana-vegetable soup. The moisture content was varied using a chicken broth prepared from chicken wings and spicy vegetables (thyme, rosemary, parsley, etc.) to improve flavor and acceptability of the extruded product. The mixture of Banana : Amaranths: pumpkins : mushrooms : carrots =40.84:40.84:9.24:3.76:5.34 was extruded at different moisture content (10–20%) and barrel temperature (100-180°C) and the effect on product responses; reconstitution potential, vitamin A retention, vitamin C, total fat among other parameters were investigated at constant screw speed (45Hz) and feed rate (50 Hz) to produce an instant banana-vegetables soup. The optimum extrusion temperature and moisture were 123.3oC and 10.122%, respectively. The optimal product had a mixture formulation of 60% extruded flour and 50% vegetable flour with chicken level at 16.6%. The overall acceptability score, fiber content, fat content, ash content, vitamin C and vitamin A values of the optimum flour were 7.1, 6.8%, 11.2%, 4.92%, 19.4 g/100 g and 1.21 mg/100 g, respectively.
Keywords: Acceptability; Extrusion; Moisture content; Temperature